POLICY EVALUATION OF NINE-YEARS LEARNING COMPULSORY OF BASIC EDUCATION: OBJECTIVES CONTEXT - Lia Amalia; Neti Karnati; Nurhatatti Fuad (STAI Hubbulwathan Duri, 2020)
The purpose of this research was to evaluate the policy of the nine-year learning compulsory of basic education from the objectives context. The research method used evaluation research approach through descriptive qualitative method. The data collection methods used interviews, observations, and documents. The data analysis technique used three stages, namely data reduction, data presentation, discussion, and drawing conclusions. The findings conclude that the objective of the nine-year compulsory education is in accordance with the government rule from the central and local governments. The methods used by the Serang government in achieving the goal of the nine-year compulsory education are the use of both natural and human resources, the participation of all parties in a comprehensive manner to carry out educational activities, and an interactive system of coordination between all parties. The implication of this research is seen in the implementation of education and management of education policies in the city of Serang.